Anti–Citrullinated Protein Antibodies Are Associated With Neutrophil Extracellular Traps in the Sputum in Relatives of Rheumatoid Arthritis Patients. Issue 6 (2nd May 2017) - Demoruelle, M. Kristen; Harrall, Kylie K.; Ho, Linh; Purmalek, Monica M.; Seto, Nickie L.; Rothfuss, Heather M.; Weisman, Michael H.; Solomon, Joshua J.; Fischer, Aryeh; Okamoto, Yuko; Kelmenson, Lindsay B.; Parish, Mark C.; et al.
Abstract : Objective: Studies suggest that rheumatoid arthritis (RA)–related autoimmunity is initiated at a mucosal site. However, the factors associated with the mucosal generation of this autoimmunity are unknown, especially in individuals who are at risk of future RA. Therefore, we tested anti–cyclic citrullinated peptide (anti‐CCP) antibodies in the sputum of RA‐free first‐degree relatives (FDRs) of RA patients and patients with classifiable RA. Methods: We evaluated induced sputum and serum samples from 67 FDRs and 20 RA patients for IgA anti‐CCP and IgG anti‐CCP, with cutoff levels for positivity determined in a control population. Sputum was also evaluated for cell counts, neutrophil extracellular traps (NETs) using sandwich enzyme‐linked immunosorbent assays for protein/nucleic acid complexes, and total citrulline. Results: Sputum was positive for IgA and/or IgG anti‐CCP in 14 of 20 RA patients (70%) and 17 of 67 FDRs (25%), including a portion of FDRs who were serum anti‐CCP negative. In the FDRs, elevations of sputum IgA and IgG anti‐CCP were associated with elevated sputum cell counts and NET levels. IgA anti‐CCP was associated with ever smoking and with elevated sputum citrulline levels. Conclusion: Anti‐CCP is elevated in the sputum of FDRs, including seronegative FDRs, suggesting that the lung may be a site of anti‐CCP generation in this population. The association of anti‐CCP with elevated cell counts and NET levels in FDRs supports a hypothesis that local airway inflammation and NET formation may drive anti‐CCP production in the lung and may promote the early stages of RA development. Longitudinal studies are needed to follow the evolution of these processes relative to the development of systemic autoimmunity and articular RA.